How Ethical Leadership Prompts Employees’ Voice Behavior? The Roles of Employees’ Affective Commitment and Moral Disengagement - Cheng, Jin; Sun, Xin; Lu, Jinting; He, Yuqing (Frontiers in Psychology, 2022)
Previous literature has demonstrated that ethical leadership could predict employees’ voice behavior. However, it’s not clear how to heighten these positive effects of ethical leadership on employees’ voice behavior. Building on the AET and moral disengagement studies, we developed an integrated model. A three-wave field study (N=232) investigated the relationship between ethical leadership and voice behavior by focusing on the mediating role of employees’ affective commitment and the moderating role of employees’ moral disengagement. Our matched data analysis results indicated that (1) employees’ affective commitment partly mediated the relationship between ethical leadership and employees’ voice behavior. In addition, employees’ moral disengagement moderated (2) the effect of ethical leadership on employees’ affective commitment and (3) the effect of employees’ affective commitment on voice behavior, similarly, (4) the indirect effect of ethical leadership on employees’ voice behavior via employees’ affective commitment. Theoretical and practical implications of these results are discussed.